2011
DOI: 10.1155/2011/513659
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression and Methylation Signatures ofMAN2C1are Associated with PTSD

Abstract: Abstract. As potential regulators of DNA accessibility and activity, epigenetic modifications offer a mechanism by which the environment can moderate the effects of genes. To date, however, there have been relatively few studies assessing epigenetic modifications associated with post-traumatic stress disorder (PTSD). Here we investigate PTSD-associated methylation differences in 33 genes previously shown to differ in whole blood-derived gene expression levels between those with vs. without the disorder. Drawin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 34 publications
(66 reference statements)
2
47
0
Order By: Relevance
“…In one investigation, transgene expression of Man2C1 promoted tumor progress in mice (18); later it was found that Man2C1 overexpression could attenuate PTEN function in prostate cancer cells (20). Con- relative to control subjects (43). None of these reports, however, successfully tied these phenotypic consequences with the Man2C1 enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…In one investigation, transgene expression of Man2C1 promoted tumor progress in mice (18); later it was found that Man2C1 overexpression could attenuate PTEN function in prostate cancer cells (20). Con- relative to control subjects (43). None of these reports, however, successfully tied these phenotypic consequences with the Man2C1 enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in inflammatory gene expression that have been described in individuals with PTSD are coincident with alterations in epigenetic markers, as immune-related methylation profiles are altered in PTSD (Heinzelmann and Gill, 2013). Methylation of mannosidase, alpha class 2C, member 1 (MAN2C1), acid phosphatase 5 (ACP5), and tolllike receptor (TLR) 8, which are genes involved in immune function, was found to be altered in PTSD Uddin et al, 2011). Decreased methylation of immune-related genes TLR1 and TLR3 has also been described in individuals with PTSD in a manner related to the severity and burden of the traumatic event (Uddin et al, 2010).…”
Section: Ptsd and Inflammationmentioning
confidence: 97%
“…[35][36][37] when accounting for individual income or exposure to stressful or adverse circumstances. 6,9,10 Living in neighborhoods characterized by residential racial segregation is associated with a greater risk of depression and anxiety, compared to living in less segregated neighborhoods.…”
Section: Aberrant Dna Methylation Signatures Characterize Mental Disomentioning
confidence: 99%